Penerapan Pendekatan Supervisi Kolaboratif Untuk Meningkatkan Kompetensi Profesional Guru di SDN Majungan Kecamatan Pademawu Kabupaten Pamekasan Tahun Pelajaran 2020/2021 - Busahri Busahri (Journal on Education, 2023)
The purpose of this study was to find out the Application of the Collaborative Supervision Approach to Improve Teacher Professional Competence at SDN Majungan, Pademawu District, Pamekasan Regency, 2020/2021 Academic Year. The research method used in this research is the School Action Research (PTS) method with the Kemmis and Mc. Taggart which is a development model of Kurt Lewin's model. From the results of this study, it was possible to increase the professional competence of teachers at SDN Majungan, Pademawu District, Pamekasan Regency for the 2020/2021 academic year from pre-cycle to cycle 1 of 18.18 points. The average teacher professional competence in the pre-cycle was 52.27 with less criteria and in cycle 1 it was 70.45 with sufficient criteria. The teacher's professional competence also increased from cycle 1 to cycle 2 by 18.19 points. The average teacher professional competence in cycle 2 was 88.64 with good criteria. So, it can be concluded that the professional competence of teachers at SDN Majungan, Pademawu District, Pamekasan Regency for the 2020/2021. Academic Year can be improved through the application of a collaborative supervision approach. Keywords: Picture And Picture, Material, Locomotor